Detection of leukemia gene fusions on DNA-level through targeted Next-Generation Sequencing - Bin Chen; Zhihui Gao; Long Chen; Hong Zhang; Yani Lin; Jing Li (PLoS ONE, 2025)
Background Targeted Next-Generation Sequencing (tNGS) is commonly used to detect genetic mutations in patients with leukemia on DNA-level, necessitating additional methods to confirm genomic rearrangements and gene fusions, resulting in a substantial sample volume requirement and significant labor expenses. Methods A novel custom leukemia tNGS panel, independently developed by Sino-US Diagnostics Lab, includes all exons from 302 genes closely associated with leukemia and 95 introns from 26 genes, thereby facilitating the detection of gene fusion alterations on DNA-level. Additionally, the common breakpoint regions of IGH and MYC are employed for the detection of IGH or MYC rearrangements. Commercial quantitative reverse transcription polymerase chain reaction (qRT-PCR) reagents were used simultaneously to detect 45 gene fusions in RNA samples. A total of 357 adults diagnosed with leukemia were included in the study. Results The qRT-PCR method detected a total of 102 gene fusions, encompassing 23 distinct types. The tNGS method identified the same gene fusions on DNA-level in 98 samples, achieving a Positive Percent Agreement (PPA) of 96.1% (98/102) when compared to the qRT-PCR method, and no false positive findings. Additionally, it revealed the presence of two gene fusions, KMT2A::ELL and KMT2A::MLLT3, which had gone undetected by qRT-PCR. The tNGS can also identify IGH or MYC gene rearrangements in patients with B-ALL, achieving a PPA of 93.8% (15/16) when compared to the FISH. Moreover, tNGS can accurately identify the specific partner genes associated with these rearrangements, facilitating a more precise analysis of the impact of mutations on prognosis. Conclusion This study confirms the feasibility of employing tNGS methods to concurrently identify gene mutations and fusions (including IGH and MYC rearrangements) at the DNA level in adults with leukemia.